Alarming implications: severe fever with thrombocytopenia syndrome and its biological vectors in the context of climate change - Ze Chen; Manoj Baranwal; Albert A. Rizvanov; Albert A. Rizvanov; Mohammed Okely; Svetlana F. Khaiboullina; Svetlana F. Khaiboullina (Frontiers in Microbiology)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonotic disease. Since its identification in China in 2009, reports of SFTS cases have steadily increased, posing a significant threat to public health. This review summarizes the epidemiological characteristics of SFTS and its biological vectors, with a particular emphasis on the role of the tick vector Haemaphysalis longicornis in disease transmission. We also addressed the impact of climate change on the spread of SFTS and its biological vectors. With continued climate change, the spread of SFTS is likely to increase, consequently heightening the risk of infection. Furthermore, this review explores the prevention and control strategies for SFTS as well as future research directions, summarize the public health policies and the alleviation of the disease's impact on human health.